2019
DOI: 10.3389/fphar.2019.00790
|View full text |Cite
|
Sign up to set email alerts
|

Metacaspases: Potential Drug Target Against Protozoan Parasites

Abstract: Among the numerous strategies/targets for controlling infectious diseases, parasites-derived proteases receive prime attention due to their essential contribution to parasite growth and development. Parasites produce a broad array of proteases, which are required for parasite entry/invasion, modification/degradation of host proteins for their nourishment, and activation of inflammation that ensures their survival to maintain infection. Presently, extensive research is focused on unique proteases termed as “met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 83 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…Though we have only evaluated the level of BiP mRNA, the upregulation in its expression can still be considered as an indicator of ER stress in Pbtmem33(−) parasites (Figure S2b). Since ER stress results in the activation of ERAD and UPR, which in turn regulates cell death pathways like apoptosis and autophagy (Peng et al., 2021), we checked the mRNA expression of autophagy (ATGs) and apoptosis (metacaspases) related genes (Kamil et al., 2019; Kamil, Atmaca, et al., 2022; Vandana et al., 2019). Our preliminary qPCR data showed that TMEM33 deletion results in the generation of ER stress which upregulated the expression of autophagy‐related genes in the malaria parasites (Figure S2c); however, no effect was observed in the expression of apoptosis marker genes (Figure S2d).…”
Section: Discussionmentioning
confidence: 99%
“…Though we have only evaluated the level of BiP mRNA, the upregulation in its expression can still be considered as an indicator of ER stress in Pbtmem33(−) parasites (Figure S2b). Since ER stress results in the activation of ERAD and UPR, which in turn regulates cell death pathways like apoptosis and autophagy (Peng et al., 2021), we checked the mRNA expression of autophagy (ATGs) and apoptosis (metacaspases) related genes (Kamil et al., 2019; Kamil, Atmaca, et al., 2022; Vandana et al., 2019). Our preliminary qPCR data showed that TMEM33 deletion results in the generation of ER stress which upregulated the expression of autophagy‐related genes in the malaria parasites (Figure S2c); however, no effect was observed in the expression of apoptosis marker genes (Figure S2d).…”
Section: Discussionmentioning
confidence: 99%
“…[73][74][75] Plasmodium species are reported to possess caspases like genes, the metacaspases, which induce apoptosis-like death. [76][77][78] Exposure to compound-17 increased the activity of caspase-3, a crucial enzyme of apoptosis. The apoptosis was confirmed by measuring markers such as DNA damage (TUNEL assay) and phosphatidylserine externalisation assay.…”
Section: Measurement Of Phosphatidylserine Externalisationmentioning
confidence: 99%
“…Artemisinin-based combination therapies are the gold standard treatment, when correctly employed [24]. Considerable effort has been made for the development of new malaria treatment as the potential use of "metacaspases", the unique proteases absent in humans [30]. Tafenoquine was recently registered to treat Plasmodium vivax.…”
Section: Malaria Cycle Vaccine and Treatmentmentioning
confidence: 99%